Peningkatan Penguasaan Kosakata Bahasa Jepang Menggunakan Media Pembelajaran Macthcard - Kapoh, Ruty Jacoba; Harahap, Putri Bintang Pratiwi (KIRYOKU, 2023)
This study aims to determine the effectiveness of the use MacthCard learning media in Goi lessons on the mastery of Japanese vocabulary of 3rd semester high school students at Universitas Negeri Manado. The type of research used is included in quasi experiments with a pretest posttest control group design.. The analysis technique used was t-test statistical analysis. From the results of the study, it is known that the use of MacthCard card games in improving the development of Japanese vocabulary acquisition skills compared to conventional learning shows a significant difference.